Application of a Synergetic Model to Assess the Effectiveness of Retraining and Advanced Training of Aviation Personnel. Issue 2 (December 2021) - M., Gudkov; A., Neveskii; O., Oleksenko; H., Khudov; Y., Solomonenko; Y., Dziubenko; O., Poliakova; O., Chernavina; Razumna, Razumna; A., A.
No abstract available